Remarks at Annual Conference of the Parliamentary Network on the World Bank, March 16, 2007 - Wolfowitz, Paul (World Bank, Washington, DC, 2019)
Paul Wolfowitz, President of the World Bank, discussed governance and anticorruption being at the heart of Africa’s development future. He spoke of donor coordination and IDA’s work in the region.